Water Quality and Sediment Profile in Shrimp Culture with Different Sediment Redox Potential and Stocking Densities Under Laboratory Condition - Wiyoto Wiyoto; Sukenda Sukenda; Enang Harris; Kukuh Nirmala; Daniel Djokosetiyanto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Sediment quality has been considered as one of the prime factors influencing the environment quality that support maximum shrimp production.The aim of the study was toevaluate the effects of sediment redox potential and shrimp stocking density on the profile of some sediment and water quality parameters. Two factors randomized factorial design was applied, with stocking density (60 and 120 shrimps.m-2) as the first variable and sediment redox potential (-65 mV, -108 mV and -206 mV) as the second variable. Some significant changes in TP, total Mn, and total S concentrations in the sediment were observed after the experimentation (P<0.05). Sediment redox potential significantly affected the dissolved oxygen, TAN, NO2, NO3, and H2S concentrations in the water. Whereas shrimp stocking density affected all water quality parameters except H2S concentration. Significant interactions between redox potential and stocking densities were observed in the nitrite and alkalinity concentrations. The significant effects of both shrimp density and redox potential on the sediment and water parameters in particular those that are known to directly affect the shrimp welfare (e.g. oxygen, ammonia, nitrite and H2S) indicate that these variables are of important aspects in shrimp pond management. Furthermore, the results clearly showed that -206mV redox potential significantly reduced the dissolved oxygen concentration in the sediment-water interface and increased the generation of H2S in water column. Thereby, this redox potential level is not advisable for shrimp culture system. Keywords: redox potential, stocking density.